(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
Seven questions on the rights of religious or belief minorities and how to measure them ABSTRACT: This paper is the outcome of a research project titled "Atlas of religious or belief minority rights" (atlasminorityrights.eu) which is aimed at mapping and measuring the rights of religious or belief minorities in the EU countries. It discusses some fundamental issues about the legitimacy, opportunity and usefulness of protecting and promoting the rights of these minorities. This is a very sensitive issue that is being addressed in an innovative way. One question concerns the possibility of measuring, through quantitative analysis applied to the world of norms, the respect for and promotion of these rights to provide an objective basis for policies aimed at granting special rights to minorities. SOMMARIO: 1. Rispetto e promozione dei diritti delle minoranze: qual è la differenza? 2. Diritti speciali per le minoranze? 3. Minoranze di religione e di convinzione: una identica tutela? 4. Queste minoranze richiedono una protezione specifica? 5. La nozione di minoranza è un "colonial construct" che non ha senso al di fuori del mondo occidentale? 6. È possibile misurare i diritti delle minoranze? 7. Qual è il rapporto tra minoranze, pluralismo e democrazia?